Effects of Self-Regulation Skills and Peer Collaboration on Laboratory Learning Satisfaction: Mediated by Laboratory Safety - Balila, Edwin; Sarno, Mormie Joseph; Garduque, Viola; Arit, Leocadio; Galang, Myrnille; Del Mundo, Rei Jeuz; Diaz, Veronica; Mercado, Giovani (12th International Scholars Conference 2025, 2026)
This mediation study examined the effects of peer and self-regulation skills on laboratory learning satisfaction as mediated by laboratory safety among students at the Adventist University of the Philippines. A total of 189 students (121 females, 68 males) aged 17-44 years from the College of Dentistry, College of Health, and College of Nursing, who were enrolled in Biochemistry and General Inorganic with Organic Chemistry during the first semester of the 2024-2025 collegiate year, participated in the study. Using structural equation modeling (SEM), the research investigated both direct and indirect paths of peer collaboration and self-regulation on ‘Laboratory Learning Satisfaction’ through ‘Laboratory Safety’ as a mediator. Results revealed significant positive effects of both peer collaboration (β = 0.234, t = 3.98, p < 0.001) and self-regulation skills (β = 0.487, t = 5.02, p < 0.001) on ‘laboratory safety.’ Laboratory safety, in turn, significantly predicted laboratory learning satisfaction (β = 0.481, t = 7.21, p < 0.001). The mediation analysis demonstrated that laboratory safety partially mediates the effects of peer collaboration and Laboratory learning Satisfaction (indirect effect: β = 0.234, t = 3.98, p < 0.001) as well as between self-regulation skills and Laboratory learning Satisfaction (indirect effect: β = 0.12, t= 3.36, p < 0.001). The total effects showed that self-regulation skills had a stronger overall impact on laboratory learning satisfaction (β = 0.619, t = 10.2, p < 0.001) compared to peer collaboration (β = 0.234, t = 3.98, p < 0.001). These findings suggest that fostering collaborative learning environments and self-regulatory skills enhances students' laboratory safety awareness, which subsequently increases their satisfaction in laboratory courses.